Phylogenetic analysis of Mycobacterium massiliense strains having recombinant rpoB gene laterally transferred from Mycobacterium abscessus. - Byoung-Jun Kim; Ga-Na Kim; Bo-Ram Kim; Tae-Sun Shim; Yoon-Hoh Kook; Bum-Joon Kim (PLoS ONE, 2017)
Recent multi locus sequence typing (MLST) and genome based studies indicate that lateral gene transfer (LGT) events in the rpoB gene are prevalent between Mycobacterium abscessus complex strains. To check the prevalence of the M. massiliense strains subject to rpoB LGT (Rec-mas), we applied rpoB typing (711 bp) to 106 Korean strains of M. massiliense infection that had already been identified by hsp65 sequence analysis (603 bp). The analysis indicated 6 smooth strains in M. massiliense Type I (10.0%, 6/60) genotypes but no strains in M. massiliense Type II genotypes (0%, 0/46), showing a discrepancy between the 2 typing methods. Further MLST analysis based on the partial sequencing of seven housekeeping genes, argH, cya, glpK, gnd, murC, pta and purH, as well as erm(41) PCR proved that these 6 Rec-mas strains consisted of two distinct genotypes belonging to M. massiliense and not M. abscessus. The complete rpoB sequencing analysis showed that these 6 Rec-mas strains have an identical hybrid rpoB gene, of which a 478 bp partial rpoB fragment may be laterally transferred from M. abscessus. Notably, five of the 6 Rec-mas strains showed complete identical sequences in a total of nine genes, including the seven MLST genes, hsp65, and rpoB, suggesting their clonal propagation in South Korea. In conclusion, we identified 6 M. massiliense smooth strains of 2 phylogenetically distinct genotypes with a specific hybrid rpoB gene laterally transferred from M. abscessus from Korean patients. Their clinical relevance and bacteriological traits remain to be elucidated.